PENGARUH PENGGUNAAN MEDIA BLOK PECAHAN TERHADAP HASIL BELAJAR SISWA PADA MATERI PENJUMLAHAN DAN PENGURANGAN PECAHAN DENGAN PENYEBUT BERBEDA DI KELAS V SDN GUGUS 1 GUGUAK PANJANG BARAT BUKITTINGGI - Wahyuni, Sri Nanda; Masniladevi, Masniladevi; Zen, MUlyani (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
Abstract The use of learning media in learning activities can provide opportunities for students to try and be actively involved in learning activities. This research purpose is to see how much the influence of using fraction block media on student learning outcomes in addition and subtraction fraction material with different denominators in grade 5. This type of research is quasi-experimental. This research was conducted at SD N 01 Benteng Pasar Atas Bukittinggi. This research is using non-equivalent control group design. The sampling technique used was purposive sampling. The data analysis technique in this study uses a prerequisite test in the form of normality and homogeneity tests along with hypothesis testing using the t-test. This reseach indicates that there is an effect of the use of fraction block media on student learning outcomes proven from the results of hypothesis testing using the t-test at a significant level α = 0.05 and df = 64 obtained by tcount of 2.190 and ttable of 2,0003.Keyword : fraction block media , Learning Outcome